Development and interplay of metabolic and mechanical performance determinants over an annual training period in adolescent national-level squad swimmers - Keller, S.; Ji, S.; Feuerbacher, J. F.; Dragutinovic, B.; Schumann, M.; Wahl, P. (International Journal of Sports Physiology and Performance, 2023)
Purpose: The study examined the longitudinal interplay of anthropometric, metabolic, and neuromuscular development related to performance in adolescent national-level swimmers over 12 months.